Effectiveness of Using Google Form-Based Evaluation Media in Islamic Religious Education Learning in End of Semester Assessment (PAS) - Sef, Widad; Asep Saepul Hamdani; Irma Soraya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In this digital era, Information and Communication Technology plays a crucial role in the world of education, which requires an educator to be able to combine and utilize information and communication technology in the learning process. This study aims to evaluate the effectiveness of using Google Form as an evaluation media in Islamic Religious Education (PAI) learning in class X SMA Nahdlatul Athfal Bangkalan. The research method used is quantitative-descriptive involving 10 students of class X B as research subjects. Data were collected through interviews, documentation, and questionnaires containing 16 questions about students' experiences in using Google Form for evaluation. The results of the study showed that the use of Google Form in PAI evaluation helps students understand the material, makes the learning process more interesting, and increases learning motivation. Evaluation with Google Form is also considered more efficient and can reduce the level of cheating during exams. These findings suggest that Google Form is an effective and practical tool to use in learning evaluation in the digital era.